Modalities and Mechanisms of Treatment for Coronavirus Disease 2019 - Zuo, Zhihong; Wu, Ting; Pan, Liangyu; Zuo, Chenzhe; Hu, Yingchuo; Luo, Xuan; Jiang, Liping; Xia, Zanxian; Xiao, Xiaojuan; Liu, Jing; Ye, Mao; Deng, Meichun (Frontiers in Pharmacology, 2021)
Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is spreading rapidly throughout the world. Although COVID-19 has a relatively low case severity rate compared to SARS and Middle East Respiratory syndrome (MERS), it is a major public concern because of its rapid spread and devastating impact on the global economy. Scientists and clinicians are urgently trying to identify drugs to combat the virus with hundreds of clinical trials underway. Current treatments could be divided into two major part: anti-viral agents and host system modulatory agents. On one hand, anti-viral agents focus on virus infection process. Umifenovir blocks virus recognizing host and entry. Remdesivir inhibits virus replication. Chloroquine and hydroxychloroquine involve preventing the whole infection process, including virus transcription and release. On the other hand, host system modulatory agents are associated with regulating the imbalanced inflammatory reaction and biased immune system. Corticosteroid is believed to be commonly used for repressing hyper-inflammation, which is one of the major pathologic mechanisms of COVID-19. Convalescent plasma and neutralizing antibodies provide essential elements for host immune system and create passive immunization. Thrombotic events are at high incidence in COVID-19 patients, thus anti-platelet and anti-coagulation are crucial, as well. Here, we summarized these current or reproposed agents to better understand the mechanisms of agents and give an update of present research situation.